Humans of New York (St. Martin's Press, 2013)
"Based on the blog with more than a million loyal fans, a beautiful, heartfelt, funny, and inspiring collection of photographs capturing the spirit of a city. In the summer of 2010, photographer Brandon Stanton set out on an ambitious project: to single-handedly create a photographic census of New York City. Armed with his camera, he began crisscrossing the city, covering thousands of miles on foot, all in an attempt to capture New Yorkers and their stories. The result of these efforts was a vibrant blog he called "Humans of New York," in which his photos were featured alongside quotes and anecdotes. The blog has steadily grown, now boasting more than a million devoted followers. Humans of New York is the book inspired by the blog. With four hundred color photos, including exclusive portraits and all-new stories, Humans of New York is a stunning collection of images that showcases the outsized personalities of New York. Surprising and moving, printed in a beautiful full-color, hardbound edition, Humans of New York is a celebration of individuality and a tribute to the spirit of the city. With 400 full-color photos and a distinctive vellum jacket"--